Estrangeirização da aquisição de terras: direito internacional ao investimento e a (in) segurança alimentar - Lima, Renata Reis de (2019)
Inserted in a specific context of crisis convergence (food, environmental, climate, energy and financial), the growth of world demand for land has become a global phenomenon in the first decade of the 21st century. At first, due to the volatility and instability of the agricultural commodity markets, the land grabbing phenomenon was analyzed by the first research developed as a way to guarantee food security. Already in a second moment, the foreignization of the acquisition of land is approached in the most diverse forms and with the most varied motives: financial speculation, control of biological or mineral energy resources, transportation routes, water sources or simply the search for new opportunities for profit through production. When considering the acquisition of land by foreigners as a potential asset for investment insurance, it is proposed to verify whether international investment agreements are compatible with international human rights law and, therefore, what their impact on security to feed. Therefore, the methodology used for the accomplishment of this research is qualitative and exploratory. More specifically, documentary research has been conducted, based on reports, documents and instruments of international organizations such as the FAO, the World Bank and IFAD, as well as non-governmental organizations. The research is also supported by a comprehensive bibliographical research, using articles published in journals of different areas of knowledge, especially the productions of Olivier De Schutter, Special Rapporteur of the United Nations for the right to food from 2008 to 2014. Thus, in the In order to legitimize this discourse, international organizations, such as the World Bank, the FAO Food Security Committee and the United Nations Conference on Trade and Development, are pushing the world land rush to affirm that it is possible to invest in and thus promote positive consequences for society, the environment and local food standards. However, it is concluded that the damage effects of global commodification of land prevail, by threatening food security and sovereignty, generating displacement of communities, changing the local productive structure and thus the way of life of collectivities.